Protection of customary land rights: Meta-Analysis and Regulatory Impact Assessment in Indonesia's New Capital (Open Society Conference, 2024)
The objective of this study is to evaluate the effectiveness of existing protection measures in safeguarding indigenous land rights in Sepaku and Samboja, East Kalimantan, within the context of the capital city of Indonesia. This study employs a comprehensive methodology, including a literature review, legal analysis, and field investigations. It examines the legal framework, institutional coordination, and impact of land use policies on indigenous communities. The data were collected via interviews and document analysis. This study reveals a pressing need to strengthen regulatory design and law enforcement to protect indigenous land tenure rights. This text highlights the challenges faced by indigenous peoples due to deforestation, land disputes, and the transformation of land for urban development. The research underscores the necessity of improved cross-sectoral authority and coordination within the Ministry of Environment and Forestry. This study provides valuable insights into the complex issues surrounding land tenure rights and indigenous communities in the context of the capital city of Nusantara. The text contributes to the ongoing discourse on environmental protection, indigenous rights, and the sustainability of land use policies in Indonesia. The findings provide practical recommendations for enhancing legal protection and mitigating deforestation in high-demand land areas, ultimately benefiting both the environment and local communities.